The modern aspects of anaphylaxis therapy - Puletić Neda M.; Milijašević Boris Ž. (Srpsko lekarsko drustvo, 2016)
Introduction: Anaphylactic reaction is a most serious allergy where the symptoms may occur shortly after contact with an allergen and can get worse quickly. Therefore, timely and appropriate treatment is of crucial importance. Methods: In this article, we draw on evidence from publications on the subject of anaphylaxis treatment that we got by searching Google Scholar and PubMed databases. Used articles included: systematic reviews, case reports and randomised controlled trials. We also used World Allergy Organization guidelines for the management and the assessment of anaphylaxis. A literature search with the keywords 'anaphylaxis treatment', 'anaphylactic shock', and 'allergy' identified a number of potentially eligible studies, of which 42 satisfied our eligibility criteria and were therefore included in this review. Topic: There was evidence regarding the optimum route, dose and site of adrenaline administration ,with the latest recommendations indicating the intramuscular route (i.m.) in the mid-outer thigh as the optimum treatment. We found studies suggesting the purpose of applying H1 and H2 antihistamines, systemic glucocorticosteroids, calcium and methylxantines to manage anaphylactic shock, recommended doses and mode of administration. With regard to treatment, we focused on acute rather than on long-term management. Further, we have taken into consideration the mechanisms, common triggers and clinical manifestations of anaphylaxis. Conclusion: Adrenaline represents the first choice drug and it is necessary to be applied as soon as possible. However, there is a controversy regarding the application of the other specified medications in this life-threatening condition.